Security studies an introduction - Williams, Paul 1975-; McDonald, Matt (Routledge, 2023)
Security Studies: An Introduction, 4th edition, is the most comprehensive textbook available on the subject, providing students with in-depth coverage of traditional and critical approaches and an essential grounding in the debates, frameworks, and issues of the contemporary security agenda.
Keywords: Sicherheitspolitik; Internationale Politik; Strategische Stabilität; Lehrbuch